Pengembangan Kurikulum Berbasis Kompetensi Era Digital dalam Pendidikan Agama Islam: Systematic Literature Review - Robiatul Adawiyah Ramadhani; Abu Warasy Batula; Nurlaila Turohmah; Antiti Armilah; Yahya Rafi Sya’bani (PT. Student RIhlah Indonesia, 2026)
The global transformation of education toward a competency-based paradigm in the digital era demands a curriculum redesign that is responsive to technological advancements and 21st-century learning needs; however, its implications for Islamic Religious Education (PAI) have not been systematically mapped. This study aims to map global trends in digital-era competency-based curriculum development and formulate their implications for PAI through a systematic literature review (SLR) approach combined with bibliometric analysis. Scopus data from the 2020–2025 period yielded 2,754 documents; bibliometric analysis using VOSviewer was applied to the entire dataset, while 18 selected articles were analyzed further using NVivo 12 Plus. The results identify five thematic clusters and eight principles of curriculum development: contextual relevance, authentic assessment, digital literacy integration, flexibility and personalization, data-driven curriculum, character and ethics reinforcement, problem-based collaborative learning, and AI and digital pedagogy integration. Based on these findings, this study proposes a Digital Competency-Based PAI Curriculum Model that integrates spiritual-religious, social-ethical, and digital-adaptive competencies, while introducing the concepts of Islamic digital literacy and digital adab as a new contextualization in the PAI curriculum rooted in the values of the Qur'an and Hadith. These findings provide a foundation for educational policymakers to revise PAI competency standards to systematically integrate digital literacy and 21st-century competencies.